Demographic Change and Federal Systems: Some Preliminary Results for Germany - Helmut Seitz; Dirk Freigang; Gerhard Kempkes (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2005)
The paper examines the effects of demographic change on federal, state and local government expenditures in Germany. Public spending is decomposed into almost 30 categories (functions) and simple estimates of age cost profiles are derived. Using population forecasts and assuming timeinvariant age cost profiles we estimate the effects of the ageing of the Germany society on the level and structure of expenditures at the three layers of governments. Our results show that subnational governments - state and local governments - can expect demographic savings whereas the federal government will live to see a worsening of its fiscal stance. Thus one should expect that significant vertical expenditure imbalances will arise that - if institutional settings are left unchanged - will ask for an adjustment of revenue distribution within the federation.
Keywords: J1; H7; H1; 330; Fiscal Federalism; Demographic Change; Vertical Fiscal Imbalances; Öffentliche Ausgaben; Finanzföderalismus; Prognose; Alternde Bevölkerung; Deutschland